The effects of risedronate treatment on the pain and the quality of life [Rizedronat tedavisinin aǧre ve yaşam kalitesi üzerine etkileri] - (:unkn) unknown (My University, 2009)
Aim: Osteoporosis is a skeletal system disease characterised by pain, physical disability and increased fracture risk which negatively effect quality of life. The aim of this study is to investigate the effects of risedronate treatment on pain and the quality of life at 6th and 12th months. Material and Methods: Eighty patients with osteoporosis were included the study and randomized into two groups. Thirty seven patients in the first group were given 35 mg weekly Risedronate and 600 mg elemantary calcium and 400IU vitamin D daily, 34 patients in the second group were given 600 mg elemantary calcium and 400IU vitamin D daily. Visual analogue scale, Beck depression scale and Notthingham health profile were completed to patients at the beginning of the treatment and at the end of the first year. Results: There was significant pain relief in both groups at 6 and 12 months. However, this was more prominent in the treatment group. It was defined that the significant decrease in the Beck depression scores was occured at the 6th month and continued at the end of the first year. In the assesment quality of life test, there was no difference before and after the treatment in the control group but we obtained significant difference in the treatment group. Conclusion: Improving the quality of life and decrease in the pain levels of the osteoporosis patients can be provided by risedronate treatment.
Keywords: Depression; Osteoporosis; Pain; Quality of life; Risedronate